2020
DOI: 10.1016/j.nbd.2020.104959
|View full text |Cite
|
Sign up to set email alerts
|

Disrupted inhibitory plasticity and homeostasis in Fragile X syndrome

Abstract: Fragile X Syndrome (FXS) is a neurodevelopmental disorder instigated by the absence of a key translation regulating protein, Fragile X Mental Retardation Protein (FMRP). The loss of FMRP in the CNS leads to abnormal synaptic development, disruption of critical periods of plasticity, and an overall deficiency in proper sensory circuit coding leading to hyperexcitable sensory networks. However, little is known about how this hyperexcitable environment affects inhibitory synaptic plasticity. Here, we show that … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
7
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 11 publications
(8 citation statements)
references
References 60 publications
1
7
0
Order By: Relevance
“…We found that, after controlling for age and general ability, the chromatin-related group performed significantly better than the synaptic-related group on the selective attention task, but groups did not differ in spatial short-term memory or longer term recognition. These findings are in line with current models of synaptic regulatory mechanisms and genetic disorders and their effects on attentional control (29, 30). For instance, poorer performance in tasks requiring inhibitory control have been reported in Fragile X Syndrome (FXS), in children and adults, supported both in cross-sectional and longitudinal studies (15, 31-33).…”
Section: Discussionsupporting
confidence: 90%
“…We found that, after controlling for age and general ability, the chromatin-related group performed significantly better than the synaptic-related group on the selective attention task, but groups did not differ in spatial short-term memory or longer term recognition. These findings are in line with current models of synaptic regulatory mechanisms and genetic disorders and their effects on attentional control (29, 30). For instance, poorer performance in tasks requiring inhibitory control have been reported in Fragile X Syndrome (FXS), in children and adults, supported both in cross-sectional and longitudinal studies (15, 31-33).…”
Section: Discussionsupporting
confidence: 90%
“…A strong consensus points to a decline in several aspects of GABAergic inhibition in FXS, see reviews by Paluszkiewicz et al (2011), Filice et al (2020), Van der Aa and Kooy (2020), and Nomura (2021) and manipulations that enhance GABAergic inhibition can alleviate several behavioral deficits in animal models of FXS and autism (Olmos-Serrano et al, 2011;Selimbeyoglu et al, 2017;Goel et al, 2018) as well as in experimental models of elevated cortical E-I balance (Yizhar et al, 2011); see reviews by D' Hulst and Kooy (2007), Cellot and Cherubini (2014), Lozano et al (2014), and Braat and Kooy (2015). Paradoxically, however, pharmacological treatment that enhances GABAergic transmission has not yet yielded clearly positive effects in patients with FXS (Ligsay et al, 2017;Van der Aa and Kooy, 2020); furthermore, some aspects of GABAergic inhibition are enhanced, instead of reduced, in the Fmr1-KO mice (Cea-Del Rio et al, 2020;Yang et al, 2020).…”
Section: Introductionmentioning
confidence: 99%
“…Previous research suggests that FMRP has a role in the development of nociceptive pain sensitization and chronic pain (23,24), and is studied as a potential target for pain treatment (25). FMR1 knockout mice that produce no FMRP show decreased neuropathic pain, protection from nociceptive sensitization (26)(27)(28) or IL-6 induced allodynia (29), and protection from pain-induced emotional sequelae such as depression (24). FMRP is hypothesized to mediate translational control over allodynia and persistent nociceptive sensitization (29).…”
Section: Introductionmentioning
confidence: 99%